PELATIHAN MICROSOFT WORD GURU-GURU TK KOTA YOGYAKARTA - Erfanti Fatkhiyah; Prita Haryani (LPPM IST AKPRIND Yogyakarta, 2022)
The development of information technology and computers that are growing rapidly, has an impact on the community, they begin to use information technology to support their daily activities, as well as teachers. Information technology and computers support the performance of teachers, especially kindergarten teachers. The ability to use office software and surf the internet is quite diverse, so to improve these skills, computer training (especially office and internet) is needed for kindergarten teachers, especially those who join in GOPTKI Yogyakarta City. This training is expected to increase the knowledge and skills of kindergarten teachers in operating the office (especially Microsoft Word and Power Point) and browsing the internet. The training was carried out offline and directly with a computer at 3Th Campus of the Institut Sains & Teknologi AKPRIND Yogyakarta. Observations at the end of the training Most of the teachers were more skilled in using word and power point and browsing for information, both written and pictures on the internet for support the performance of teachers in managing administration and making learning media. Keywords: kindergarten teachers, computer training, GOPTKI Yogyakarta City